The impact of martial law on the observance and protection of human rights and freedoms - Nitsevych, Olesia; Voloshanivska, Tetiana; Lepei, Olena; Danylo, Serhii (DIXI, 2025)
The relevance of the scientific research conducted in this article stems from the fact that the observance and protection of human rights and freedoms are of particular importance under martial law. Under such conditions, all spheres of society, socio-economic, political, and cultural undergo a conceptual restructuring and adaptation to address urgent security issues. This implies granting additional powers to state authorities, military command, and law enforcement agencies solely to ensure the smooth functioning of the state apparatus under conditions of uncertainty, thereby minimizing the risks of destabilizing the internal situation. Naturally, this affects the observance and protection of human rights and freedoms, since any restrictions imposed under the legal regime of martial law must comply with the provisions of the Constitution of Ukraine, Ukrainian laws, and international legal acts ratified by Ukraine. The digitalization of public services is particularly important for ensuring the observance and protection of human rights and freedoms under martial law, as it involves maximally simplifying interactions between the population and public authorities amid the challenges posed by regular shelling, electricity shortages, and air raids. The development of digital technologies under martial law was largely facilitated by previous experience in adapting state institutions to remote work during the COVID-19 pandemic. Despite the potential restrictions on human rights and freedoms under the martial law regime, the activities of public authorities should be carried out in accordance with the principle of legality and within the powers provided by applicable law.